2017
DOI: 10.1016/j.anifeedsci.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yellow mealworm larvae (Tenebrio molitor) inclusion in diets for female broiler chickens: implications for animal health and gut histology

Abstract: 49The aim of the present study was to evaluate the animal 50 performance, haematochemical parameters, intestinal 51 morphology and histological features of broiler chickens fed 52 diets including Tenebrio molitor (TM) larvae meal. A total of 53 160 female broiler chicks (Ross 708) at one-day of age were 54 randomly allotted to four dietary treatments: a control (C) 55 group and three TM groups, in which TM meal was included at 56 50, 100 and 150 g/kg, respectively. Each group consisted of 57 five pens as repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
91
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 38 publications
17
91
1
2
Order By: Relevance
“…A quadratic response was observed for large intestines, which was not expected. For all the other internal organs, there were no significant dietary effects, which is in agreement with several studies that have reported a lack of dietary effects on the size of internal organs of broiler quails fed BSFL meal [23] and broiler chickens fed mealworm [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A quadratic response was observed for large intestines, which was not expected. For all the other internal organs, there were no significant dietary effects, which is in agreement with several studies that have reported a lack of dietary effects on the size of internal organs of broiler quails fed BSFL meal [23] and broiler chickens fed mealworm [13].…”
Section: Discussionsupporting
confidence: 91%
“…Inclusion of insect larvae meal in broiler diets decreased the incidence of metabolic skeletal disorders while improving bird health [11]. Positive effects of Tenebrio molitor and Hermetia illucens meals on broiler production and health have also been reported by Oyegoke et al [12] and Biasato et al [13]. In contrast, there is no information on the effect of feeding insect meals to Jumbo quails, presumably because these birds are relatively new entrants into the commercial poultry production sector.…”
Section: Introductionmentioning
confidence: 98%
“…there has been a growing interest in various insect species as potential dietary protein sources. Dietary supplementation with dried mealworm (Tenebrio molitor) larvae has already been tested in fish, pigs and broiler chickens [2,6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Insect-derived products are considered to be one of the most promising sources in animal nutrition, as they can effectively substitute not only conventional proteins (Biasato et al, 2016(Biasato et al, , 2017(Biasato et al, , 2018Gasco et al, 2016;Renna et al, 2017;Roncarati et al, 2015;Stadtlander et al, 2017), but also lipids (Schiavone et al, 2017a, in press). Moreover, insect-derived products can stimulate the immune system and thus sustain animal health (Bovera et al, 2015;Henry et al, 2018;Spranghers et al, 2018;Vogel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%